Water Birds in the Marzgrove Forest of Cimanuk River Delta - Mustari, Abdul Haris (Media Konservasi, 2011)
The mangrove forest in the Cimanuk delta plays an important role as feeding ground, shelter, breeding and many social activities of water birds in the northern coast of West Java. During 3 months research, 28 species of water birds were found in this delta and 12 species of them are migrant water birds. Illegal hunting, destruction of the mangrove forest and intensive use of pestisides and insectisides in the fish ponds in this delta threaten the population of the water birds.